Reliability of the Single-Leg, Medial Countermovement Jump in Youth Ice Hockey Players - Anthony S. Donskov; Jeffrey S. Brooks; James P. Dickey (MDPI AG, 2021)
Appropriate performance tests are critical for documenting training, fatigue and injury-related changes. Functional performance testing can provide quantitative information on specialized sport movements. The single-leg, medial countermovement jump is an objective measure of frontal plane force, velocity and power, and is particularly applicable for ice hockey players given that ice skating involves applying lateral forces. This study assessed the short-term reliability (10 days) of the single-leg, medial countermovement jump performed by ten competitive male youth ice hockey players. Each participant performed three right and three left maximal single-leg, medial countermovement jumps from force plates. Measured variables included lateral and vertical takeoff velocity, lateral and vertical maximal force, maximal force above bodyweight, lateral and vertical peak concentric power, average concentric power, and average concentric power during the last 100 ms of push-off. Relative reliability was quantified by intraclass correlations. Absolute reliability and the smallest real difference were also calculated. The single-leg, medial countermovement jump had moderate-to-excellent test-retest reliability (ICC: 0.50-0.98) for all twelve variables of interest. These results suggest that the single-leg, medial countermovement jump is a reliable test for assessing frontal plane force, velocity and power in ice hockey players, and is a valid functional performance test for this population given the similarity to ice skating.